2019
DOI: 10.1002/celc.201801774
|View full text |Cite
|
Sign up to set email alerts
|

Core‐Shell Structure of SnO2@C/PEDOT : PSS Microspheres with Dual Protection Layers for Enhanced Lithium Storage Performance

Abstract: Abundant material SnO2 is considered as a promising lithium‐ion battery (LIB) anode candidate due to its high theoretical capacity. Yet, the achieved capacity is restricted by the severe cycling degradation. Rational structural design can mitigate the volume expansion of SnO2, improving the structural stability and reaction kinetics at the same time. Herein, core‐shell structured SnO2@C/PEDOT : PSS microspheres are synthesized through a facile approach combined with hydrothermal treatment and polymerization. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…The polymeric shell not only enhances the structural stability of the electrode material but also can be engineered to contribute to the pseudocapacitance, further boosting the energy storage capabilities. This is the widest application for this type of material, with successful use in electrochemical capacitors, lithium–sulfur batteries, rechargeable lithium batteries, ,, energy storage, , and supercapacitor electrodes . One example of this is the work of Zhou et al, which presents the development of core–shell structured S@PPy NPs sandwiched in graphene sheets, aimed at enhancing the performance of lithium–sulfur batteries .…”
Section: Applications Of Conductive Core–shell Nanoparticlesmentioning
confidence: 99%
“…The polymeric shell not only enhances the structural stability of the electrode material but also can be engineered to contribute to the pseudocapacitance, further boosting the energy storage capabilities. This is the widest application for this type of material, with successful use in electrochemical capacitors, lithium–sulfur batteries, rechargeable lithium batteries, ,, energy storage, , and supercapacitor electrodes . One example of this is the work of Zhou et al, which presents the development of core–shell structured S@PPy NPs sandwiched in graphene sheets, aimed at enhancing the performance of lithium–sulfur batteries .…”
Section: Applications Of Conductive Core–shell Nanoparticlesmentioning
confidence: 99%
“…The PDA-coated SnO 2 [117] with a layer thickness of 5 nm exhibited significantly improved cycling stability and demonstrated good cyclability for over 300 cycles. Li et al reported a facile approach combined with hydrothermal treatment and polymerization to fabricate the core-shell-structured SnO 2 @C/PEDOT:PSS micro-sphere anodes, as seen in Figure 7a [126]. For a better understanding of structural changes during cycling, the TEM images of the SnO 2 @C anode after 200 cycles at a current rate of 0.5 C are depicted in Figure 7b,c.…”
Section: Snomentioning
confidence: 99%
“…By mechanical and implicitly electronic contact with other coated particles it can also enhance electron transport across the electrode. A typical example is the use of a PEDOT:PSS shell around a SnO 2 core (Li et al 2019e). Overall performance improvements, in particular a major stability improvement, were reported.…”
Section: Auxiliary Components and Functionsmentioning
confidence: 99%